Educational Services for Early Childhood: Hyperactive Child Behavior Management in Kindergarten - Putri, Risti Andriana; Waluyo, Edi (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Early childhood education services are designed to be inclusive and accessible to all groups without discrimination based on background, race, ethnicity, religion, or other differences. This study aims to analyze early childhood education services in handling hyperactive children's behavior in kindergarten environments. This study uses a qualitative descriptive method, with data collected through observation, interviews, and document analysis. The number of responses in this study was 7 people including school principals, teachers and child developmental psychologists. The implementation of the study involved 2 observers, namely the main class teacher, assistant teacher and researcher. Data were analyzed using the Miles and Hubermen model which consists of data collection, data reduction, data presentation and drawing conclusions. An ideal early childhood education program for children with special needs requires an inclusive, responsive approach and support that is appropriate to individual needs. The findings of this study emphasize the importance of early childhood education services in handling hyperactive children's behavior. The success of services to handle hyperactive behavior in kindergarten is evaluated through learning planning, the multifunctional role of teachers, and supporting and inhibiting factors in education. These factors need to be addressed comprehensively to ensure the success of early childhood education in supporting optimal development and learning for hyperactive children. The latest information in this study has implications for the development of science in the field of education, especially in the field of early childhood education.